An investigation into vocabulary learning strategies of grade 10 efl students at a rural school - Trà Thanh Hằng (Trường Đại học Trà Vinh, 2021)
The purpose of this study is to provide empirical evidence of students’ views of vocabulary learning strategies that they know and those they apply. There have been various studies, as presented in chapter 2, that have focused on learners’ vocabulary learning strategies. Yet, there have been few studies that have attempted to find out how EFL high school learners in rural areas like Tra Vinh learn vocabulary and what strategies they use to acquire vocabulary.